Long‐term life expectancy for children with ependymoma and medulloblastoma. Issue 11 (27th May 2015) - Frandsen, Jonathan E.; Wagner, Aaron; Bollo, Robert J.; Shrieve, Dennis C.; Poppe, Matthew M.
<x xml:space="preserve">Abstract</x> Objectives There is a paucity of long‐term follow‐up data for children with intracranial ependymoma (IE) and medulloblastoma (MB). What happens to these children 20, 30, or 40 years after diagnosis? Do they have potential for a normal lifespan? The purpose of this study was to ascertain the long‐term survival potential in children with MB or IE who have survived 5 years from diagnosis. Methods A retrospective analysis was conducted using the SEER Program. Children (ages 0–19 years) from 1973 to 2011 with a diagnosis of MB or IE were identified. A cohort was created of potentially cured patients who survived 5 years from diagnosis. Cox proportional hazards models and Kaplan–Meier estimates were utilized to analyze long‐term survival. Results We identified 876 patients with MB and 474 patients with IE who were alive 5 years from diagnosis. Patients with MB had a 30‐year overall survival (OS) and cancer‐specific survival (CSS) of 70.2% and 80.1%, respectively. Patients with IE had a 30‐year OS and CSS of 57.3% and 68.8%, respectively. When comparing MB with IE, MB had improved CSS (P = 0.04) and trended toward increased OS (P = 0.10). Conclusions A significant number of deaths due to disease occur for several decades after treatment for both IE and MB. Despite this, the potential for long‐term survival exists in 5‐year survivors of both histologies. If alive at 5 years from diagnosis, patients with MB tend to have a lower risk of death from disease compared to those with IE. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.